Implementasi Prinsip-Prinsip Hukum dalam Membangun Harmonisasi Beragama Melalui Kearifan Lokal - Warjiyati, Sri; Sari, Zeti Nofita (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The research object is the implementation of legal principles in building religious harmonization using local wisdom as the main approach and utilized to strengthen inter-religious harmony. The aim of this research is to explore the role of legal principles in Islam and local wisdom values in strengthening harmony between religious communities. The research method used is normative analysis, involving a study of Islamic legal literature and relevant local wisdom documents. The research results show that the principles of Islamic law can be integrated with local wisdom values to create an environment of mutual respect and understanding between religious believers. The discussion highlighted the importance of active community involvement in strengthening the implementation of legal principles and local wisdom in creating sustainable religious harmonization. The conclusion of this research underlines that collaboration between legal principles and local wisdom is a crucial step in efforts to build inclusive and sustainable religious harmonization.